2023
DOI: 10.1503/cmaj.230715
|View full text |Cite
|
Sign up to set email alerts
|

Canadian guideline for the clinical management of high-risk drinking and alcohol use disorder

Evan Wood,
Jessica Bright,
Katrina Hsu
et al.

Abstract: Background: In Canada, low awareness of evidence-based interventions for the clinical management of alcohol use disorder exists among health care providers and people who could benefit from care. To address this gap, the Canadian Research Initiative in Substance Misuse convened a national committee to develop a guideline for the clinical management of high-risk drinking and alcohol use disorder. Methods: Development of this guideline followed the ADAPTE process, buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 59 publications
0
19
0
6
Order By: Relevance
“…Importantly, like all diagnostic systems that depend on a standardized collection of relatively subjective criteria, there is room for scrutiny and ongoing research of the reference standard diagnosis of alcohol use disorder . For instance, when using the DSM-5 , it is critical that clinicians distinguish between mild and more severe alcohol use disorder, especially because the DSM-5 represented a marked departure from the prior biaxial model that distinguished abuse and dependence via distinct criteria . It is also important to highlight recent research implying that not all 11 DSM-5 alcohol use disorder criteria are equally informative …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, like all diagnostic systems that depend on a standardized collection of relatively subjective criteria, there is room for scrutiny and ongoing research of the reference standard diagnosis of alcohol use disorder . For instance, when using the DSM-5 , it is critical that clinicians distinguish between mild and more severe alcohol use disorder, especially because the DSM-5 represented a marked departure from the prior biaxial model that distinguished abuse and dependence via distinct criteria . It is also important to highlight recent research implying that not all 11 DSM-5 alcohol use disorder criteria are equally informative …”
Section: Discussionmentioning
confidence: 99%
“…The review’s findings should be put into context alongside a major opportunity to improve medical care and public health given that excessive alcohol use and alcohol use disorders directly contribute to a tremendous burden of morbidity and mortality, including accounting for approximately 20% of deaths in those aged 20 to 49 years in the US . Even though there are effective psychosocial and medication-based treatments that have been proven to reduce heavy alcohol use and improve rates of abstinence, they are often underused. Recent data from a large sample of Medicare Part D claims, and that specifically examined rates of medication treatment for alcohol use disorder after alcohol-related hospitalizations, found that only 1.3% of individuals initiated medication within 30 days of discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[48] Community-level programs including, but not limited to, educational campaigns and limiting availability of alcohol, training servers, and enhanced enforcement of on-premise laws and legal requirements have also been shown to reduce alcohol consumption and harm. [48] At the individual level, primary care level screening and brief interventions for hazardous and harmful alcohol use, [52] as well as therapy (both psychosocial interventions and pharmaceutical treatment) for alcohol use disorders, [53] are each associated with reductions in alcohol drinking including prolonged periods of abstinence. Their effects, however, diminish with time; thus, booster sessions are necessary for brief interventions, and among people with severe alcohol use disorders, at least 60% of those with AUD will relapse to hazardous drinking within 6 months following treatment.…”
Section: Interventions To Reduce Alcohol Usementioning
confidence: 99%
“…Their effects, however, diminish with time; thus, booster sessions are necessary for brief interventions, and among people with severe alcohol use disorders, at least 60% of those with AUD will relapse to hazardous drinking within 6 months following treatment 54 . Peer groups and aftercare can help decrease relapse rates 53 …”
Section: Interventions To Reduce Alcohol Usementioning
confidence: 99%